Dichrorampha baixerasana sp. n. (Lepidoptera Tortricidae) from Calabro-Lucano Appennine (ltaly). (Bollettino di zoologia agraria e bachicoltura, 2024)
A new Tortricidae, Dichrorampha baixerasana sp. n., is described; the species is closed to Dichrorampha senectana Guenée. The differences between the two species are in the coloration of wings, that is darker in D. baixerasana, as in the shape of valva, and in the apex of aedeagus. This last part in the new species presents an elongated projection, with 4-5 teeth, as in Dichrorampha harpeana Frey, Dichrorampha heegerana Duponchel, Dichrorampha ligulana H.-S., and in Dichrorampha sequana Hubner. In the female genitalia of D. baixerasana the colliculum is longer than that of seventh sternite with more strongly developed left wall.
Keywords: Dichrorampha baixerasana; Lepidoptera Tortricidae; new species; Souther Appennine